Early diagnosis of solitary functioning kidney: comparing the prognosis of kidney agenesis and multicystic dysplastic kidney - Flogelova, Hana; Bouchalova, Katerina; Smakal, Oldrich; Halek, Jan; Langova, Katerina; Cizkova, Katerina (Pediatric nephrology (Berlin, Germany), 2024)
BACKGROUND: Individuals with congenital solitary functioning kidney (SFK) are at an increased risk of kidney damage. According to some studies, the risk is higher in unilateral kidney agenesis (UKA) than in unilateral multicystic dysplastic kidney (UMCDK). We hypothesized that with early detection of children with UKA and UMCDK, there would be no difference in the presence of hypertension, proteinuria, and reduced glomerular filtration rate (GFR) between UKA and UMCDK. METHODS: Based on a long-term follow-up protocol, we evaluated a cohort of 160 children followed from birth for SFK (84 with UKA and 76 with UMCDK) detected by prenatal or routine neonatal ultrasound screening. Hypertension, proteinuria, and reduced GFR were monitored as markers of kidney damage. We compared the characteristics and outcomes of the subgroups of children with UKA and UMCDK. RESULTS: GFR was reduced in 42 (26.2%) children, of whom 41 showed only mild reduction. Hypertension and proteinuria were found in 22 (13.8%) and 14 (8.8%) children, respectively. Combined kidney damage was present in 57 (35.6%) children. The UMCDK and UKA subgroups differed in GFR at final examination, with UMCDK patients being significantly more likely to have normal GFR compared to UKA patients (82% vs. 67%; p = 0.039). CONCLUSIONS: One third of the children showed signs of SFK damage, albeit mild. Patients with UKA had reduced GFR significantly more often than those with UMCDK, but did not differ in the rates of hyperfiltration injury or congenital anomalies of the kidneys and urinary tract (CAKUT) in SFK.
Keywords: vrozené vady; nemoci ledvin; Proteinuria; Unilateral multicystic dysplastic kidney; Kidney; multicystické dysplastické ledviny; hypertenze; Female; Multicystic Dysplastic Kidney; Infant; předškolní dítě; dítě; novorozenec; ženské pohlaví; Glomerular Filtration Rate; Neonatal Screening; Glomerular filtration rate; lidé; Infant, Newborn; Solitary Kidney; Congenital Abnormalities; následné studie; Kidney Diseases; solitární ledvina; prognóza; časná diagnóza; CAKUT; Hypertension; Follow-Up Studies; Male; kojenec; Child, Preschool; Early Diagnosis; Prognosis; Child; mužské pohlaví; novorozenecký screening; Functional solitary kidney; Unilateral kidney agenesis; ledviny; hodnoty glomerulární filtrace; proteinurie; Humans